Projectos de investigação em História Medieval financiados pela FCT nos últimos 10 anos - Rodrigues, Ana Maria (2011)
In this article we evaluate the relative position of the research projects on Medieval History among the whole of the research projects on History, submitted for funding to the Portuguese Foundation for Science and Technology (FCT) in the last ten years. We concluded that the Middle Ages had always a discrete but equivalent position both among the applications and the approved projects; this only changed in 2008, when none of the thirteen projects on Medieval History was approved, precisely when not a single medievalist was part of the jury. We also tried to evaluate the productivity of the financed projects through an Internet search and found out that the data provided is partial and insufficient; the research teams need to make an additional effort to disclose the results of their projects in the World Wide Web and the FCT should also be more demanding concerning that issue.